Działalność Ministerstwa Wyznań Religijnych i Oświecenia Publicznego w dwudziestoleciu międzywojennym na rzecz międzynarodowej współpracy intelektualnej - Kula, Ewa; Pękowska, Marzena (Wydawnictwo Naukowe UAM, 2016)
The aim of the present study is to show the international scientific cooperation, undertaken and carried out in the interwar period (1918:1939) by the Polish Ministry of Religious Affairs and Public Education in the framework of bilateral cooperation agreements on intellectual property. The basis of the study are mainly archival sources, initiating and supporting research activities, including international cooperation, gathered in the Archives of New Records in Warsaw. The publication presents the state and the scope of the agreements and conventions adopted by countries such as France, Belgium, Yugoslavia, Romania, Bulgaria, Hungary, and Sweden. The organization of work committees and subcommittees appointed to implement these agreements, the areas of the activity of these committees, plans, and the effects of this activity are also shown. The material presented is an introduction to further research on the issue of the exchange of science and higher education as well as secondary education in international intellectual cooperation.
The Activity of the Ministry of Religious Denominations and Public Education in the Interwar Period for he Sake of International Intellectual Cooperation
Keywords: international intellectual cooperation; education; science; international agreements; the Ministry of Education